PALATAL EXPANSION WITH SIX BANDS: an alternative for young adults - Ribeiro, Gerson Luiz Ulema; Retamoso, Luciana Borges; Moschetti, Ariana Bridi; Mei, Raul Magnoler Sampaio; Camargo, Elisa Souza; Tanaka, Orlando Motohiro (Archives of Oral Research, 2009)
crossbite. METHOD: Opening of the midpalatal suture using a tooth-and-tissue-borne expander. RESULTS AND DISCUSSION: Rapid maxillary expansion (RME) is the preferred procedure in growing patients because it allows stability with respect to the amount of bone expansion and it avoids teeth expansion. In adults it is frequently associated with failure. However, in individuals past their growth spurt where the midpalatal suture and adjacent circumaxillary articulations have become more rigid, surgically assisted rapid maxillary expansion is recommended. The original Haas expander appliance consists of bands fitted to the first molars. Increased anchorage with bands on the second premolars enhances the orthodontic effect and can be used successfully in patients beyond their skeletal growth spurt. CONCLUSION: A non surgical alternative for treating transverse maxillary deficiency with skeletal crossbite in patients after their growth spurt, using a modified Haas palatal expander with six bands is presented.